Guest commentary: globalisation and emerging nations – conceptualisation of the Asian crisis - Christopher T. Selvarajah (Penerbit Universiti Kebangsaan Malaysia, 1999)
This article discusses the impact of ‘the Asian Crisis’ as explained within a globalising environment. Within this context, consequently, the Asian Crisis itself has been identified as part of the on-going globalisation process. This article begins by tracing the emergence of many East Asian nations in terms of their rapid economic growth and development, contrasts East Asian versus Western models of economic development, describes the evolution of Asian versus colonial economic institutions, and traces the of the Asian Tigers, Japan, ASEAN-4 and the People’s Republic of China. It culminates with the events that ensued during the Asian Crisis of mid-1997 to 1998. Five “wild cards” or key factors, advocated to contribute to a resolution of this regional crisis are then discussed. The author concludes with a call to the international community to tackle the free flow of speculative investments, to determine the type and amount of acceptable foreign direct investment, and to determine the form of selective intervention that best suits an individual country’s development, to avoid economic instability and impoverishment